Water Versus Dry Planting : a Synthesis of Three Month Survival Data for 58 Pinus patula Research Trials - Rolando, C. A.; Crous, J. (Indian Forester, 2007)
Despite the implementation of many trials, there is no consensus as to whether plant Pinus patula seedlings with water improves survival over those planted without water. This is partly a function of the isolation of research in time, as well as the site specific nature of the trials, each reflecting the environmental and climatic conditions at implementation. To address this, a dataset of 58 trials incorporating a dry-planted and water-planted treatment was established to determine whether trends in three month survival existed. The trials incorporated into the dataset were all planted to P. patula between 1990 and 2005 in the summer rainfall region of southern Africa. Data pertaining to the climate, local weather, physiography and site management at each trial were included. Summary statistics, linear correlation and multiple regression were used to determine if any of the site-associated variables were related to survival in the dryplanted and water-planted treatments. The analyses indicated that the average percentage survival was lowest during the summer months, regardless of treatment. Planting with water was most likely to increase survival when used during spring, autumn and winter planting. Linear correlation and multiple regression did not highlight any significant relationships between site-associated variables and survival in the dry-planted and water-planted treatments.